The Ecology of Multilevel Interventions to Reduce Social Inequalities in Health. (August 2013) - Trickett, Edison J.; Beehler, Sarah
Health inequities persist and, in some cases, are increasing. Multilevel interventions involve efforts to change aspects of social contexts related to the creation and maintenance of health inequities among varied groups. Momentum for conducting multilevel interventions to achieve health equity is found across professional fields as well as scientific and funding organizations. This article discusses the rationale for multilevel interventions, briefly reviews their evolution over time with respect to health inequities, and provides an ecological "way of thinking" about some of the conceptual and pragmatic challenges they raise for social science. This perspective frames community interventions as multilevel, ecologically based, collaboratively conducted, culturally situated, and designed to increase community capacity. Implications of this perspective are drawn for the development, implementation, and evaluation of multilevel interventions.